Information Disruption in Online Journalism in the Era of the Industrial Revolution 5.0 - Lestari, Anna Puji; Fitri, Fitri (Universitas Semarang, 2021)
This study examines the barriers to online journalism in the 5.0 industry era in facing market competition. This research was conducted on suaramerdeka.com as a large newspaper company in Central Java that can still survive in the midst of global competition in the mass media competition. Critical perspective with Fairclough's Critical Discourse Analysis design used in this study. The novelty of this research is specifically to answer the challenges of online journalism in the era of the industrial revolution 5.0 in terms of human resources. The findings of this study are related to the routine of news production in the suaramerdeka.com media, the speed of news updates, the accuracy and balance of the news. The human resources of news seekers and editing teams are not yet fully prepared to face the challenges of the new era. The results of this study shows that 1) the news production dependent on HR factor, company factor and managing editor; 2) the news delivery planning dependent on the market need, the news content of the printed Suara Merdeka aims at fulfilling the needs of the people of Central Java, suaramerdeka.com seeks to meet the needs of the people of Central Java around the world.